THE RELATIONSHIP BETWEEN EMOTIONAL MATURITY AND SELF-ACCEPTANCE OF GRADE X STUDENTS AT SMA NEGERI 5 BOGOR - Muhammad Azzami Nurwaskita; Imas Kania Rahman; Noneng Siti Rosidah (Yayasan Amanah Nur Aman, 2026)
This study aims to determine the relationship between emotional maturity and self-acceptance among tenth-grade students at SMA Negeri 5 Bogor. Emotional maturity refers to an individual’s ability to manage and express emotions appropriately, while self-acceptance refers to the ability to accept oneself fully, including both strengths and weaknesses. This study employed a quantitative approach with a correlational method. The population consisted of 383 students, with 196 participants selected through probability sampling using a simple random sampling technique. Data were collected using emotional maturity and self-acceptance questionnaires that had been tested for validity and reliability, and analyzed using SPSS version 31.0.2.0. The results showed that most students were in the moderate category for emotional maturity (75.5%) and self-acceptance (70.9%). The product moment correlation test revealed a correlation coefficient of 0.691 with a significance value of 0.001 < 0.05, indicating a strong positive relationship between emotional maturity and self-acceptance. This means that higher emotional maturity is associated with higher self-acceptance, and vice versa. Based on these findings, schools are encouraged to develop systematic and sustainable programs through guidance and counseling services and other structured interventions to improve students’ emotional maturity and self-acceptance. Further research is advised to develop studies with other relevant research methods and variables.